Potency and Conservation of Aren (Arenga pinnata (Wurmb) Merr.) in Meru Betiri National Park, East Java-Indonesia - Ervizal A. M. Zuhud; Primadhika Al Manar; Zuraida; Syafitri Hidayati (Jurnal Manajemen Hutan Tropika, 2020)
Aren (Arenga pinnata (Wurmb) Merr.) is a high ecological and economical value species of Indonesia. Aren grows spreading in Indonesia including at Meru Betiri National Park in the province of East Java, Indonesia. The community in Meru Betiri National Park uses aren fruit which is called kolang-kaling. Even though aren grows naturally in this area, the community has not maximized its utilization. This study aims to identify the actual and ideal conditions for aren conservation also to analyse the gap between them, and to formulate the conservation actions to realize a sustainable aren conservation in Meru Betiri National Park. The data wascollected by using vegetation analysis and in-depth interviews with all of the aren farmers. Aren regeneration in Meru Betiri National Park is categorized stable and seems to be decreased. The use of aren by the community is limited only from the fruit as kolang-kaling. There is a gap between current and ideal conditions for achieving aren sustainability. To achieve the ideal conditions, conservation actions are needed among aren farmers by utilizing agroforestry systems, increasing the value of aren, intensive coaching for aren farmers, and forming a group of aren farmer.